Development of a new efficient rebar - V. V. Filippov; A. B. Steblov; V. P. Berzhanin; D. V. Lenartovich; O. G. Miijugin (Литьë и металлургия)
The main principles of creation of a new kind of rolled metal for reinforcement of reinforced concrete ware are formed